Concrete with high salt corrosion resistance and preparation method thereof
By using the formula of modified polycarboxylic acid water reducing agent, gas induction agent, ion chelating agent, polyacrylamide, sodium methyl silicate and multi-wall carbon nanotubes in the concrete, a concrete with high salt corrosion resistance is formed, which solves the problem of damage to the durability of existing concrete in the composite salt corrosion environment and achieves a better salt corrosion resistance.
Patent Information
- Application Number
- CN202411886625.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
Existing concrete is difficult to effectively resist the complex interactions of different salt ions in the composite salt erosion environment, resulting in damage to structural durability.
A highly salt-resistant concrete is used, and its formulation includes silicate cement, slag powder, gravel, machined sand, modified polycarboxylic acid water reducing agent, gas induction agent, ion chelating agent, polyacrylamide, sodium methyl silicate and multi-wall carbon nanotube dispersion. Through the synergistic effect of these components, a dense microstructure and a strong ionic barrier are formed to enhance the anti-salt corrosion performance.
It significantly improves the anti-chlorine and sulfate corrosion properties of concrete in composite salt erosion environments, extends the service life of the structure, and provides more reliable infrastructure guarantees.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to high salt corrosion resistance concrete and a preparation method thereof. Background Art
[0002] In actual engineering, concrete structures are exposed to moist soil, seawater or industrial wastewater pollution for a long time, and will inevitably suffer from complex compound salt erosion. The salt components in these environments are not only diverse, such as sodium chloride, sodium sulfate, magnesium salts, etc., but also the concentration changes periodically with factors such as seasons and tides, forming a dynamic erosion environment. This complex salt erosion poses a serious threat to the durability of concrete structures.
[0003] Traditional methods for concrete to resist salt erosion mainly focus on the following aspects: adding mineral admixtures to fill pores and improve the density of concrete; adding admixtures such as water reducers and air entraining agents to improve the microstructure of concrete; and applying waterproofing agents or other protective layers on the surface of concrete. However, most of these methods target the erosion of a single salt, while in a complex salt erosion environment, complex interactions may occur between different salt ions, such as co-precipitation and ion exchange, thereby accelerating the deterioration of concrete. In addition, the crystallization and dissolution process of salts in the pores of concrete will produce repeated volume changes, causing cracks in the concrete, providing channels for the penetration of harmful substances such as chloride ions.
[0004] Based on the above problems, designing and preparing a concrete with excellent salt corrosion resistance in a composite service environment has become an urgent problem to be solved. Summary of the invention
[0005] In response to the above technical problems, the present invention provides a highly salt-resistant concrete under complex service environments and a preparation method thereof, which effectively prolongs the service life of concrete structures and provides reliable protection for infrastructure construction.
[0006] In order to achieve the above purpose, the technical solutions adopted are as follows:
[0007] A highly salt-resistant concrete and a preparation method thereof, comprising the following components:
[0008] Cement 300~400kg / m 3 , slag powder 50~150kg / m 3 , Crushed stone 1000~1200kg / m 3 , Machine-made sand 650~800kg / m 3 , modified polycarboxylic acid water reducing agent 0.5~2kg / m 3 , air entraining agent 0.005~0.01kg / m 3 , ion chelating agent 0.05~0.1kg / m3 , polyacrylamide 0.05~0.1kg / m 3 , sodium methyl silicate 0.01~0.05kg / m 3 , Multi-walled carbon nanotube dispersion 0.1~0.5kg / m 3 , Water 140~160kg / m 3 .
[0009] According to the above scheme, the cement is silicate cement or ordinary silicate cement, the strength grade is not less than 42.5, the initial setting time is not less than 120 minutes, and the other properties meet the requirements of "General Portland Cement" GB 175-2007.
[0010] According to the above scheme, the specific surface area of the slag powder is not less than 400m 2 / kg, 28d activity index is not less than 95%, and other properties meet the requirements of "Granulated blast furnace slag powder for cement, mortar and concrete" GB / T 18046-2017.
[0011] According to the above scheme, the crushed stone is 5.0mm~31.5mm continuously graded crushed stone, and its performance meets the requirements of "Crushed Stone and Pebbles for Construction" GB / T 14685-2022.
[0012] According to the above scheme, the parent rock of the artificial sand is limestone, dolomite, granite or quartzite, the medium sand in Zone II has a fineness modulus of 2.6 to 2.8, and the performance meets the requirements of "Construction Sand" GB / T 14684-2022.
[0013] According to the above scheme, the modified polycarboxylic acid water-reducing agent has a solid content of 40% to 50%, a water reduction rate of 15% to 20%, and a density of 1.05 to 1.15 g / cm 3 , pH value is 6-8; other properties meet the requirements of "Concrete Admixtures" GB 8076-2008;
[0014] The molecular structure of the modified polycarboxylate water reducer is as follows:
[0015]
[0016] Among them, a is 3 to 6, and b is 2 to 20.
[0017] According to the above scheme, the air entraining agent is one of rosin air entraining agent and alkylbenzene sulfonate air entraining agent or a mixture of the two, and the effective solid content is not less than 98%; the other properties meet the requirements of "Concrete Admixtures" GB 8076-2008.
[0018] According to the above scheme, the method for preparing the ion chelating agent comprises the following steps:
[0019] Dissolve maleic anhydride in deionized water, start heating and slowly add 30% hydrogen peroxide solution, continue stirring for 15-30 minutes; then slowly drop 10% sodium hydroxide solution to adjust the pH value of the system to between 7.5 and 8.5, maintain the reaction temperature at 90-95°C and stir for more than 23 hours, finally stir and cool to room temperature to obtain the ion chelating agent;
[0020] The invention comprises 5 to 10 parts of maleic anhydride, 60 to 70 parts of deionized water, 2 to 5 parts of 30% hydrogen peroxide solution and 20 to 25 parts of 10% sodium hydroxide solution by weight; the amount of calcium ions chelated by the ion chelating agent is 800 to 1000 mg / g.
[0021] According to the above scheme, the polyacrylamide is a white powder with a molecular weight of 50,000 to 100,000 and a density of 1.25 to 1.35 g / cm 3 .
[0022] According to the above scheme, the sodium methyl silicate is a colorless or light yellow transparent liquid with a solid content of 30±1% and a density of 1.1-1.3 g / cm 3 .
[0023] According to the above scheme, the multi-walled carbon nanotube dispersion is obtained by ultrasonic dispersion of multi-walled carbon nanotubes, a dispersant and water, and the concentration is 10 wt%.
[0024] The method for preparing the above-mentioned highly salt-resistant concrete comprises the following steps:
[0025] (1) mixing a modified polycarboxylic acid water reducer, an air entraining agent, an ion chelating agent, polyacrylamide, sodium methyl silicate and a portion of mixing water to obtain an admixture mixture;
[0026] (2) Putting crushed stone, cement, machine-made sand, the admixture mixture, the multi-walled carbon nanotube dispersion and the remaining mixing water into a mixer in sequence and stirring for 2 to 3 minutes to obtain highly salt-resistant concrete.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The modified polycarboxylate water-reducing agent in the admixture introduces an organic amine substance with a special side chain functional group. The organic amine substance undergoes a polymerization reaction with the polycarboxylate water-reducing agent, resulting in an extension of the original chain length and an increase in the number of short chains. These short chains and long chains alternate and entangle with each other in the spatial structure; at the same time, some organic amine molecules are dispersed in the main chain and side chains, filling the gaps between the side chains and improving the spatial steric hindrance; in addition, the unreacted organic amine molecules can accelerate cement hydration and enhance the density of concrete. The above reasons make the microstructure in the concrete more compact and enhance the resistance to sulfate corrosion.
[0029] (2) The air-entraining agent in the admixture can introduce a certain amount of bubbles, reduce its internal friction, play a ball effect, and improve the fluidity of concrete. At the same time, the bubbles can absorb some moisture, which can reduce the bleeding and segregation of concrete. The bubbles produced by the air-entraining agent can fill the pores in the concrete, reduce the channels for water and harmful substances to penetrate, reduce the entry of sulfate ions into the concrete, improve the concrete's impermeability, and reduce the erosion of sulfate on the concrete.
[0030] (3) The ion chelating agent in the admixture has good adaptability to the modified polycarboxylate water reducer and cement, and has good adaptability to Ca 2 + Mg 2+ , Fe 2+ It has a strong chelating effect on metal ions such as calcium and magnesium ions. It can form water-soluble chelates with calcium and magnesium ions, and then migrate to pores and cracks in a humid environment, react with unhydrated cement or other active substances to produce crystalline products, improve the pore structure of concrete, increase its density, and thus limit Cl - 、SO4 2- Plasma diffuses from the outside into the concrete.
[0031] (4) The polyacrylamide in the admixture mainly plays a role in water retention and bonding. It can absorb some moisture, delay the drying shrinkage of concrete, and reduce the generation of microcracks. At the same time, it forms a three-dimensional network structure in the concrete, effectively hindering the penetration of water and salt solutions, and improving the anti-permeability. Sodium methyl silicate hydrates in concrete to form calcium silicate hydrates, filling the pores of concrete, forming a dense structure, and thus improving the resistance to salt erosion. Polyacrylamide and sodium methyl silicate work synergistically to form a double protective barrier at both the physical and chemical levels, hindering the migration of external salt erosion ions and improving the concrete's resistance to salt erosion.
[0032] (5) The multi-walled carbon nanotubes in the ultra-dispersed multi-walled carbon nanotube solution have a fiber bridging effect, making the cement paste structure in the concrete more compact, reducing holes and cracks, and improving the toughness and strength of the concrete; at the same time, the multi-walled carbon nanotubes can also promote the growth of cement hydration products, increase the formation of high-density calcium silicate gel, reduce the generation and development of microcracks in the concrete, and further optimize the original porosity and pore size distribution. However, due to the good electrical conductivity of carbon nanotubes, a conductive path will be formed inside the concrete, accelerating the corrosion rate of chloride ions, thereby having a negative impact on the concrete's resistance to chloride ion corrosion. The introduction of sodium methyl silicate can improve the ion barrier effect of concrete, reduce the effective concentration of chloride ions in concrete, and inhibit the electrochemical reaction between chloride ions and carbon nanotubes. In addition, sodium methyl silicate may also react with calcium hydroxide (Ca(OH)2) in cement to form hydrated silicate (CSH) gel, providing a stronger passivation protective layer for the steel bars, which helps to further reduce the penetration of chloride ions and the electrochemical corrosion process, and reduce the negative impact of the electrical conductivity of carbon nanotubes on the durability of concrete. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0034] The specific implementation method provides a high salt corrosion resistance concrete and a preparation method thereof, which is composed as follows:
[0035] Cement 320~400kg / m 3 , slag powder 50~150kg / m 3 , Crushed stone 1000~1200kg / m 3 , Machine-made sand 650~800kg / m 3 , modified polycarboxylic acid water reducing agent 0.5~2kg / m 3 , air entraining agent 0.005~0.01kg / m 3 , ion chelating agent 0.05~0.1kg / m 3 , polyacrylamide 0.05~0.01kg / m 3 , sodium methyl silicate 0.01~0.05kg / m 3 , Multi-walled carbon nanotube dispersion 0.1~0.5kg / m 3 , Water 140~160kg / m 3 Unless otherwise specified, all raw materials used were commercially available.
[0036] The specific implementation method provides a structural formula of a modified polycarboxylate water reducer and a preparation method thereof:
[0037] The solid content of modified polycarboxylic acid water-reducing agent is 40% to 50%, the water reduction rate is 15% to 20%, and the density is 1.05 to 1.15 g / cm 3 , pH value is 6 to 8; other properties meet the requirements of "Concrete Admixtures" GB 8076-2008. The molecular structure of the modified polycarboxylic acid water reducer is as follows:
[0038]
[0039] The preparation method of the modified polycarboxylic acid water-reducing agent is as follows: in a nitrogen atmosphere, acrylic acid and polyethylene glycol monomethyl ether acrylate are added to deionized water, stirred and dissolved, heated to 70-90°C, and then sodium persulfate solution (initiator) is added dropwise, and the reaction is maintained for 2-3 hours to form a basic polycarboxylic acid mother liquor; then, an organic amine compound is reacted with isocyanate at 60-80°C to form a modified organic amine monomer substance; finally, the prepared modified organic amine monomer is gradually added to the basic polycarboxylic acid mother liquor, the temperature is maintained at about 80°C, and the temperature is lowered to room temperature after 1-2 hours of reaction. The molar ratio of acrylic acid, polyethylene glycol monomethyl ether acrylate, organic amine compound and isocyanate is 1:0.25:0.2:0.2, and the initiator is 0.1% of the molar amount of maleic anhydride.
[0040] The specific embodiment provides an ion chelating agent and a preparation method thereof:
[0041] First, maleic anhydride is added into deionized water to completely dissolve to form a uniform solution, then heated and slowly added with 30% hydrogen peroxide solution, and continued to stir for 15-30 minutes; then 10% sodium hydroxide solution is slowly added dropwise to adjust the pH value of the system to between 7.5 and 8.5, the reaction temperature is maintained at 90-95° C. and stirred for reaction for 23 hours, and finally stirred and cooled to room temperature to obtain the ion chelating agent; the raw materials used are calculated by weight: 5-10 parts of maleic anhydride, 60-70 parts of deionized water, 2-5 parts of 30% hydrogen peroxide solution and 20-25 parts of 10% sodium hydroxide solution; the amount of calcium ions chelated by the obtained ion chelating agent is 800-1000 mg / g.
[0042] Specific embodiments provide a multi-walled carbon nanotube dispersion, which is obtained by ultrasonically treating multi-walled carbon nanotubes, a dispersant and water at 20° C. and 40 Hz for 10 minutes, and has a concentration of 10 wt %.
[0043] The air entraining agent used in the specific implementation is an alkylbenzene sulfonate air entraining agent.
[0044] The polyacrylamide used in the specific implementation has a molecular weight of 70,000 and a density of 1.3 g / cm 3 .
[0045] The sodium methyl silicate used in the specific implementation is a light yellow transparent liquid with a solid content of 30% and a density of 1.23 g / cm 3 .
[0046] The technical solution of the present invention is compared with ordinary salt erosion resistant concrete, the total amount of cementitious materials of each strength grade concrete remains unchanged, and the amount of fine aggregate, crushed stone, admixture and water in each strength grade concrete is kept fixed, and the blank group benchmark ratio is shown in Table 1. The specific components and amounts of the embodiments of the present invention and the comparative examples are shown in Table 2.
[0047] The raw materials in Table 1 are of conventional types, among which the mineral powder is of grade S95, and its technical performance meets the relevant requirements of GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete"; the crushed stone adopts conventional 5.0mm-31.5mm continuous graded crushed stone, and the other properties meet the requirements of GB / T 14685-2022 "Crushed stone and pebbles for construction"; the machine-made sand adopts conventional limestone or pebbles to make machine-made sand, medium sand in zone II, and fineness modulus is 2.8, and the other properties meet the requirements of GB / T 14684-2022 "Construction sand"; the ordinary admixture composition used in blank group 1 includes 0.7kg / m 3 , slump-preventing agent 0.2kg / m 3 , air entraining agent 0.006kg / m 3 , white sugar 0.05kg / m 3 , sodium gluconate 0.05kg / m 3 ; The common admixture composition used in blank group 2 includes water reducing agent 1.0kg / m 3 , slump retaining agent 0.24kg / m 3 , air entraining agent 0.007kg / m 3 , white sugar 0.08kg / m 3 , sodium gluconate 0.08kg / m 3 The common admixture used in blank group 3 includes 1.3 kg / m 3 , collapse-preventing agent 0.30kg / m 3 , air entraining agent 0.01kg / m 3 , white sugar 0.1kg / m 3 , sodium gluconate 0.1kg / m 3 .
[0048] Table 1 Blank group 1-3 ordinary salt erosion resistant concrete mix information (kg / m 3 )
[0049] Serial number Strength level cement Slag powder gravel Machine-made sand Water consumption Common admixtures 1 C40 300 50 1100 800 160 1.0 2 C50 350 70 1100 750 150 1.4 3 C60 400 100 1080 700 140 1.8
[0050] Table 2: Mix ratio information of high salt corrosion resistance concrete of examples and comparative examples (kg / m3 )
[0051]
[0052]
[0053] According to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GBT 50081-2019, the compressive strength of 100 mm cube was tested. According to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" GB / T 50082-2009, the chloride ion penetration resistance and sulfate corrosion resistance tests were carried out. The electric flux and compressive strength corrosion resistance coefficient of the concrete were tested. The performance characterization results of the specific embodiment are shown in Table 3.
[0054] Table 3 Concrete performance test data
[0055] serial number 7d compressive strength / MPa 28d compressive strength / MPa Electric flux C(28d) Compressive strength corrosion resistance coefficient / % Blank group 1 35.4 42.8 1835 0.731 Blank Group 2 48.6 56.7 1433 0.783 Blank group 3 57.6 68.5 842 0.821 Example 1 38.3 47.9 1032 0.895 Example 2 36.8 45.6 985 0.902 Example 3 51.5 61.5 738 0.932 Example 4 49.8 60.8 691 0.943 Example 5 62.5 73.1 421 0.977 Example 6 60.3 71.8 407 0.983 Comparative Example 1 35.8 43.7 1473 0.814 Comparative Example 2 36.4 44.8 1635 0.799 Comparative Example 3 37.1 45.6 1596 0.826 Comparative Example 4 34.6 43.8 1744 0.781
[0056] It can be seen from the test data that with the increase of strength grade and the increase of cementitious materials in concrete, the overall durability of concrete is improved. Under the same strength grade, the high salt erosion resistance concrete of the present invention has lower electric flux and higher compressive strength corrosion resistance coefficient than the ordinary salt erosion resistance concrete of blank group 1-3, which means that it has better resistance to chloride ion and sulfate erosion. It can be seen from Example 1 and Comparative Examples 1-3 that after adding a single multi-walled carbon nanotube solution, ion chelating agent or polyacrylamide and sodium methyl silicate, the salt erosion resistance of concrete is significantly lower than that of concrete in Example 1; it can be seen from Example 1 and Comparative Example 4 that the high erosion resistance concrete prepared by using the modified polycarboxylate water reducer of the present invention has significantly better resistance to chloride ion and sulfate erosion than the ordinary polycarboxylate water reducer.
[0057] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A highly salt-resistant concrete, characterized in that The composition is as follows: Cement 300~400kg / m 3 , slag powder 50~150kg / m 3 , Crushed stone 1000~1200kg / m 3 , Machine-made sand 650~800kg / m 3 , modified polycarboxylic acid water reducing agent 0.5~2kg / m 3 , air entraining agent 0.005~0.01kg / m 3 , ion chelating agent 0.05~0.1kg / m 3 , polyacrylamide 0.05~0.1kg / m 3 , sodium methyl silicate 0.01~0.05kg / m 3 , Multi-walled carbon nanotube dispersion 0.1~0.5kg / m 3 , Water 140~160kg / m 3 .
2. The highly salt-resistant concrete according to claim 1, characterized in that The cement is silicate cement or ordinary silicate cement, with a strength grade of not less than 42.5, an initial setting time of not less than 120 minutes, and other properties comply with the requirements of "General Purpose Portland Cement" GB 175-2007.
3. The highly salt-resistant concrete according to claim 1, characterized in that The specific surface area of the slag powder is not less than 400m 2 / kg, 28d activity index is not less than 95%, and other properties meet the requirements of "Granulated blast furnace slag powder for cement, mortar and concrete" GB / T 18046-2017; The crushed stone is a continuously graded crushed stone with a diameter of 5.0 mm to 31.5 mm, and its performance meets the requirements of "Crushed Stone and Pebbles for Construction" GB / T14685-2022; The parent rock of the artificial sand is limestone, dolomite, granite or quartzite, it is medium sand in Zone II, and its fineness modulus is 2.6 to 2.8, and its performance meets the requirements of "Construction Sand" GB / T 14684-2022.
4. The highly salt-resistant concrete according to claim 1, characterized in that The modified polycarboxylic acid water-reducing agent has a solid content of 40% to 50%, a water reduction rate of 15% to 20%, and a density of 1.05 to 1.15 g / cm 3 , pH value is 6-8; other properties meet the requirements of "Concrete Admixtures" GB 8076-2008; The molecular structure of the modified polycarboxylate water reducer is as follows: Among them, a is 3 to 6, and b is 2 to 20.
5. The highly salt-resistant concrete according to claim 1, characterized in that The air entraining agent is one of rosin air entraining agent and alkylbenzene sulfonate air entraining agent or a mixture of the two, and the effective solid content is not less than 98%; the other properties meet the requirements of "Concrete Admixtures" GB 8076-2008.
6. The highly salt-resistant concrete according to claim 1, characterized in that The preparation method of the ion chelating agent comprises the following steps: Dissolve maleic anhydride in deionized water, start heating and slowly add 30% hydrogen peroxide solution, continue stirring for 15-30 minutes; then slowly drop 10% sodium hydroxide solution to adjust the pH value of the system to between 7.5 and 8.5, maintain the reaction temperature at 90-95°C and stir for more than 23 hours, finally stir and cool to room temperature to obtain the ion chelating agent; The invention comprises 5 to 10 parts of maleic anhydride, 60 to 70 parts of deionized water, 2 to 5 parts of 30% hydrogen peroxide solution and 20 to 25 parts of 10% sodium hydroxide solution by weight; the amount of calcium ions chelated by the ion chelating agent is 800 to 1000 mg / g.
7. The highly salt-resistant concrete according to claim 1, characterized in that The polyacrylamide is a white powder with a molecular weight of 50,000 to 100,000 and a density of 1.25 to 1.35 g / cm 3 .
8. The highly salt-resistant concrete according to claim 1, characterized in that The sodium methyl silicate is a colorless or light yellow transparent liquid with a solid content of 30±1% and a density of 1.1-1.3 g / cm 3 .
9. The highly salt-resistant concrete according to claim 1, characterized in that The multi-walled carbon nanotube dispersion is obtained by ultrasonic dispersion of multi-walled carbon nanotubes, a dispersant and water, and the concentration is 10 wt %.
10. The method for preparing the highly salt-resistant concrete according to any one of claims 1 to 9, characterized in that The following steps are involved: (1) mixing a modified polycarboxylic acid water reducer, an air entraining agent, an ion chelating agent, polyacrylamide, sodium methyl silicate and a portion of mixing water to obtain an admixture mixture; (2) Putting crushed stone, cement, machine-made sand, the admixture mixture, the multi-walled carbon nanotube dispersion and the remaining mixing water into a mixer in sequence and stirring for 2 to 3 minutes to obtain highly salt-resistant concrete.
Citation Information
Cited By
Compound high-fluidity concrete pumping agent and preparation method thereof
CN121426470A
High salt corrosion resistant concrete and preparation method thereof
CN122426984A